PSYCHOTRAUMATIC EXPERIENCES OF ADOLESCENTS DURING THE WAR IN UKRAINE - Yevhen Kharchenko; Liana Onufriieva (Психологічні перспективи)
Purpose of this article is to describe psychotraumatic experiences of adolescents during the war in Ukraine.